Development of Creative Independence of Design Students in Course of Higher Education - Yu.V., Daskova (2020)
Development of Russian society puts forward new requirements for the quality of training in higher educational institutions. It is necessary for a short period of training in the higher educational institution not only to transfer to student’s important professional knowledge and skills, but also to form the ability and willingness to use them creatively. This issue is especially challenging when preparing design students. Today, a promising, popular and dynamically developing profession of designer is in demand in almost all areas of life. The increased demand for individuality in the design of living space, from the planning and design of the interior or exterior to the most insignificant things, can only be satisfied by a designer who has the ability to combine, improvise and find breakthrough ideas. Therefore, there is a crucial issue of the search for teaching aids that allow students to be prepared to find the solutions of professional tasks with creative independence. The professional activity of a designer is determined by the objects and tasks, which require creative abilities, spatial visual thinking, knowledge of the graphic language for visualization of informarion. The design project is created by man and for man. This determines the importance of solving socio-cultural issues, as well as taking into account the characteristics of human perception in the design process. It requires knowledge of the natural sciences, engineering and humanities, various types of arts, architecture, literature and even music. Thus, the intra-systemic and inter-systemic connections required for the implementation of designprohects, make it more intelligent and human oriented.